Antioxidant Activity and Marker Compound Levels of Cempedak Leaf (Artocarpus integer) Extract in Different Solvent Variations - Sari, Anna Khumaira; Rizki, Muhammad Ikhwan; Azhara, Desiya Damayanti; Fadlilaturrahmah, Fadlilaturrahmah (Baiman Bauntung Batuah Center, 2024)
Cempedak (Artocarpus integer) is known to contain phenolic compounds. Phenolic compounds are secondary metabolites of plants included in marker compounds that act as natural antioxidants because they have hydroxyl groups that can reduce free radicals. Plants containing phenolic compounds are known to have strong antioxidant activity. This study aimed to determine the antioxidant activity and levels of marker compounds from ethanol extracts of cempedak leaves in various solvent variations. Cempedak leaves were dried in an oven and then powdered. Cempedak leaf powder was extracted using methanol, 70% ethanol, 96% ethanol using the maceration method, and distilled water was extracted using the boiling method. The extract was tested for antioxidant activity using the DPPH (1,1-diphenyl-2-picryl-hydrazyl) method based on the IC50 value. Determination of marker compound levels using the Folin-Ciocalteu reagent with a gallic acid comparator using a UV-Vis spectrometer instrument. The total phenolic content determination test results were expressed as gallic acid equivalents per gram of extract (GAE/g extract). The results of the antioxidant activity test showed the IC50 value of the methanol extract was 84.48 ppm (strong), the distilled water extract was 54.74 ppm (strong), the 70% ethanol extract was 72.21 ppm (strong), and the 96% ethanol extract was 24.55 ppm (very strong). The results of the marker compound determination showed the total phenolic content of the methanol extract was 28.22% w/w, the distilled water extract was 22.59% w/w, the 70% ethanol extract was 29.55%, and the 96% ethanol extract was 31.14% w/w. It can be concluded that the cempedak leaf extract extracted with 96% ethanol has very strong antioxidant properties and the highest marker compound content among other solvents. For further analysis, 96% ethanol solvent can be used for the cempedak leaf extraction.